Acupuncture protects against ischemic stroke by inhibiting the NF-κB pathway - Linlin Wang; Lanrong Chen; Jiayong Wu; Chengyan Liu; Caixia Chi; Shicong Wang (IBRO Neuroscience Reports)
Cerebral ischemia is a leading cause of disability and death worldwide. This study aims to investigate the neuroprotective effects of acupuncture on rats with middle cerebral artery occlusion (MCAO) and elucidate the underlying mechanisms involving the nuclear factor kappa-B (NF-κB) pathway and the NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome. Acupuncture at specific acupoints, i.e., GV26, GV20, and ST36, was administered to MCAO rats. Infarct volume was measured by TTC (2,3,5-triphenyl-tetrazolium chloride solution) staining. Protein expression levels of NF-κB pathway components and inflammatory markers were determined by western blot and enzyme-linked immunosorbent assay. Terminal deoxynucleotidyl transferase dUTP nick end labeling and hematoxylin-eosin staining were performed to evaluate apoptosis and histopathologic changes. Acupuncture significantly improved neurological function and reduced infarct volume in MCAO rats, as evidenced by decreased TTC staining areas. Meanwhile, acupuncture reduced NF-κB pathway, NLRP3 inflammasome and pro-inflammatory cytokines. Compared with the MCAO group, apoptotic cells were significantly reduced in the acupuncture group, which attenuated the histopathological changes induced by cerebral ischemia, including neuronal cell damage and tissue disorganization. However, application of phorbol 12-myristate 13-acetate partially reversed the beneficial effects of acupuncture, suggesting that the NF-κB pathway plays a key role in mediating the neuroprotective effects of acupuncture. Acupuncture exerts significant neuroprotective effects in MCAO rats, possibly through inhibition of the NF-κB pathway and NLRP3 inflammasome activation. These findings provide insight into the mechanisms of acupuncture in the treatment of ischemic stroke and support its potential therapeutic application.